Pulmonary arterial hypertension in Thai patients with systemic sclerosis - Suparaporn Wangkaew (2018)
Objective: Study the clinical features of pulmonary arterial hypertension (PAH) in Thai patients with systemic sclerosis (SSc), and compare these features between those with limited (lc) SSc and diffuse (dc) SSc. Material and Method: The medical records of SSc patients attending the Division of Rheumatology, Chiang Mai University were reviewed. PAH was defined by pulmonary arterial systolic pressure (PASP) > 35 mmHg, determined by Doppler echocardiography. Results: Among 275 patients with SSc, 66 had Doppler echocardiography measurement. Thirty-nine patients (59.1%) had PAH. Among the PAH-SSc patients, 36 (92.3%) presented with dyspnea on exertion, and 37 (94.8%) were in a New York Heart Association functional class of II and III. Twenty-four of 39 patients (61.5%) had interstitial lung disease. Diffuse SSc patients had a significantly higher proportion of males, and shorter disease duration between SSc and PAH diagnosis than lcSSc patients. Conclusion: PAH was not uncommon in Thai patients with SSc. Interstitial lung disease might have been the cause associated with over half of these cases. Annual routine Doppler echocardiography screening for PAH in patients with SSc may detect preclinical PAH, and lead to early management and improved functional outcome.